Active-Scanned Protons and Carbon Ions in Cancer Treatment of Patients With Cardiac Implantable Electronic Devices: Experience of a Single Institution - Seidensaal, Katharina; Harrabi, Semi Ben; Scholz, Eberhard; Ellerbrock, Malte; Haberer, Thomas; Weykamp, Fabian; Mattke, Matthias; Welte, Stefan E.; Herfarth, Klaus; Debus, Jürgen; Uhl, Matthias (Frontiers in Oncology, 2019)
Abstract Background Ionizing radiation was shown to be able to influence the function of cardiac implantable electronic devices (CIED’s) leading to malfunctions with potentially severe consequences. Those effects presumably correlate with beam energy and neutron production. Thus, restraining has been proclaimedparticle facilities are commonly cautious to for the treatment of patientstreat patients with CIED’s with particles, but substantial evidence is lacking. Methods and Materials In total 31 patients were investigated, who have been treated at the Heidelberg Ion-Beam Therapy Center (HIT) from September 2012 to February 2019 with protons and carbon ions in active-scanning technique. All CIED’s were checked after every single irradiation by the department of cardiology. The minimum distance between the CIED and the planning target volume (PTV), the 10% isodose and the single beam in Beam’s Eye View (BEV) was analyzed for 12 patients. Results In total, 31 patients received 32 courses of radiotherapy (RT). Twenty-two received treatment with carbon ion beam and ten with proton beam. The cumulative number of fractions was 582, the cumulative number of documented controls after RT was 504 (87%). Three patients had an implantable cardioverter-defibrillator (ICD) and 28 patients had a pacemaker at the time of treatment. Seven patients had a heart rate of ≤30 /min. The majority of patients (69%) were treated for tumors of the head and neck. The median minimum distance between CIED and PTV, 10 % isodose and the single beam on BEV was 13.4 cm, 11.6 cm and 8.3 cm, respectively. There were no registered events associated with the treatment in this evaluation. Conclusion Treatment of CIED-patients with protons and carbon ions applied with active raster scanning technique was safe without any incidents in our single center experience. Monitoring after almost every fraction provided systematic and extensive data. Further investigations are necessary in order to form reliable guidelines, which should consider different modes of beam application, as active scanning supposedly provides a greater level of safety from malfunctions for patients with CIED undergoing particle irradiation.